Design and evaluation of multidimensional turbo product coded MIMO-OFDM system - Muladi, Muladi (2007)
Multiple inputs multiple outputs (MIMO) realized through employing multiple antennas at both transmitter and receiver provides low bit error rate and high transmission rate as required by future digital wireless communication systems. Space time coding and spatial multiplexing are the two approaches in exploiting MIMO channel. This project proposes a new multiple inputs multiple outputorthogonal frequency division multiplexing (MIMO-OFDM) system employing single parity check multidimensional turbo product codes (MDTPC) that will provide high bit rate transmission with low bit error rate over correlated frequency selective fading channels. The initial work is developing the dimensional-based reading order (DBRO) algorithm for generating the MDTPC codeword sequences. The MDTPC codeword sequence is then applied to MIMO-OFDM system that exploits space, time, and frequency diversity and provides full-rate transmission. The system provides diversity gain of 2.5 dB in signal to noise ratio (SNR) and coding gain of 3 dB. Spatial multiplexing space-time coded MDTPC-MIMO-OFDM system with antennas grouping (AG-SMST-SPC-MDTPC-MIMO-OFDM) is then developed to increase the transmission rate. The result shows that the system provides a high transmission rate of 8 bps/Hz at SNR of 10 dB using two groups of four transmit antennas. The final task is designing the accurate channel estimation for the AGSMST- MDTPC-MIMO-OFDM system employing pilot symbol assistance and least square estimation using mean-square error criterion. The channel estimator achieves mean-square error of 7x10-4 which is highly accurate. The proposed system provides high transmission bit rate of 120 Mbps with bit error rate of 10-5 at SNR of 18 dB for two groups of four transmit antennas. It can be implemented in wireless local area network (WLAN) and can also be deployed in any broadband wireless system.